Blue Basin Waterfall and Swimming Pool, Trinidad (Hayward, Montreal)-40 - (:unkn) unknown (Photogelatine Engraving Co., Canada, 2011)
The postcard shows two young men near the Blue Basin swimming pool and Waterfall located in Diego Martin, Northwest Trinidad.
Colour: Coloured; Style: Portrait; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Diego Martin; Waterfalls--Trinidad and Tobago; Blue Basin Waterfall (Trinidad and Tobago)